Revisando a revisão : genocídio americano : a Guerra do Paraguai de J.J. Chiavenatto - Queiróz, Silvânia de (2010)
The book American Genocide: war of Paraguay, the journalist and writer Júlio José Chiavenato, 1979, was published in a troubled period of national history in the process of political opening. The book was very well accepted by the intellectual academic and liberal, seeking new forms of struggle and resistance against the dictatorship and in a few months, the American Genocide became a bestseller and a reference in the study of war in Paraguay. Moreover, the work aroused the discontent of groups linked to the military regime by criticizing the action and the memory of the army in war. The author suffered severe retaliation on the basis of the work. JJ Chiavenato presented a reinterpretation of the events of the war with Paraguay and brought new and important elements for national historiography, as the social, cultural and economic situation in Paraguay, showed the Argentine and Brazilian interests in the war, criticized the action of national heroes and showed the killing occurred in Paraguay. To understand these changes we need to understand the root causes of this conflict, which started in the process of independence in Spanish America, followed by between unitary and federalist discuss the control of the La Plata United Provinces and Buenos Aires province by elite interests dominate in Paraguay and thus realize the old dream of expanding his dominion over the whole territory of the former viceroyalty of La Plata. In reviewing the history of Paraguay, it was noted that she is very close to the vision of JJ Chiavenato, where governments of both France and Lopez were presented as wise leaders, who were forced into isolation, the Paraguayan soldiers defended not only the Solano López, but their existence as small farmers, among other elements. The study of Brazilian history, historiography Paraguayan and Argentine historiography possible to better define the concepts of each score and the similarities and differences between them. In the analysis of interviews with historians and school textbooks is clear the importance and impact that the work had over the years, forming opinions for generations. In recent years the work of JJ Chiavenato has undergone a process of legitimation, however, either positively or negatively those who work the national historiography of the war in Paraguay, will have to compulsorily quote Chiavenato JJ